ILRI Internally Commissioned External Review (ICER) on communications and information activities - International Livestock Research Institute (International Livestock Research Institute, 2003)
ILRI has recently reorganised and brought all communications and information functions under one umbrella. Management has decided to get an independent opinion on how best to move forward and to this end has commissioned an external review to assist think about information flow and managing the information and knowledge system here at ILRI. The team for this review includes Dr. Klaus von Grebmer, Director of Communications, IFPRI (ICER chairman); Ms. Jane Frances Asaba, Information Scientist, CAB International Africa Regional Centre; and Dr. Robert Stephen Day, Executive Director, ICT, University of South Africa. The terms of reference of the team is 1) Take stocks of ILRI's public awareness efforts, including media and graphic design activities and corporate appearance and identity) and advise on priorities for the future; the production, design, distribution and marketing of ILRI's publications; the library and knowledge sharing/management processes; and the institute's intranet and internet activities. 2) Assess strengths, weaknesses, opportunities and threats (SWOT) relevant to ILRI'S communication activities and outlines strategic goals (What messages? What target groups? How to reach them? What resources? What strategic partnerships?) for ILRI's communication activities; and 3) Develop an action plan on priorities and an organisational structure to achieve the desired strategic goals.. The document is divided into five; viz; CGIAR; Information; Publications; Web; and Public Awareness. The public awareness part is again divided into 24 sections.